Investigation on an outbreak of bacillary dysentery due to infection of Shigella sonnei in a town of Guangxi Province - Tian Ren; Jiang Yuyan; Lu Huan; Pei Yingxin; Tan Dongmei; Deng Qiumei; Yanxu Zhong (Elsevier, 2023)
Objective: To provide a scientific basis for identifying the causes of an outbreak and providing preventive and control measures to prevent the recurrence of similar outbreaks. Study design: A case-control study. Methods: We defined a suspected case as residents living in the affected town presented with inexplicable diarrhea (≥3 times/24 h) and at least with fever (above 37.5) or abdominal pain or vomiting from June 20 to July 14, 2016. The confirmed case was Shigella sonnei isolated from feces or rectal swabs of the suspected case. Cases were identified by reviewing medical records in different medical facilities in the affected town and interviewing physicians and cases using a questionnaire. The local water supply was checked on site. An age-matched case-control study was conducted. Epi-Info 7.0 software was used for data analysis. Results: 133 cases aged from 1 to 77 were identified with 102 suspected and 31 confirmed. The attack rate was 0.7% (133/18131). The majority of clinical manifestations were diarrhea (100%), fever (83.5%) and abdominal pain (40.6%). Among 64 case-control pairs, 64.1% cases and 18.8% of controls drank non-boiled water (OR = 7.7, 95% CI 3.5-17.0) within 15 days before their onset. 42.2% cases and 10.1% controls had the illness in family members (OR = 6.5, 95% CI 2.5-16.3). 18 samples of Shigella sonnei were isolated from 50% (4/8) faces, 40% (13/33) rectal swabs and 14% (1/7) tap water. 8 were strain-typed by PFGE and showed 100% homology in the typing pattern. No disinfection was routinely implemented for water supply, 1household latrine was found to discharge directly into the river which is used as the local water source. Conclusion: This outbreak was caused by contaminated drinking water supply with household exposure helped facilitate further transmission. Water sources should be kept clear of defecation discharge and disinfected before supply, un-boiled water drinking habits need to be addressed through health promotion.